2007
DOI: 10.1111/j.1365-2605.2007.00769.x
|View full text |Cite
|
Sign up to set email alerts
|

KIT and RAS signalling pathways in testicular germ cell tumours: new data and a review of the literature

Abstract: Testicular germ cell tumours (TGCTs) are the leading cause of cancer deaths in young male Caucasians. Identifying changes in DNA copy number can pinpoint genes involved in tumour development. We defined the smallest overlapping regions of imbalance in TGCTs using array comparative genomic hybridization analysis. Novel regions, or regions which refined those previously reported, were identified. The expression profile of genes from 12p, which is invariably gained in TGCTs, and amplicons defined at 12p11.2-12.1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
91
1
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(106 citation statements)
references
References 75 publications
13
91
1
1
Order By: Relevance
“…These were GCT27, GCT44, Tera1, Tera2, H12.2, 2102Ep, 577MF, NTERA2, SUSA and TCam-2. The cell lines were cultured as described previously (Pera et al, 1987;Kelland et al, 1992;Mizuno et al, 1993;Summersgill et al, 2001;Goddard et al, 2007). A pool of 45 individual samples of normal testis RNA was available from Clontech (Mountain View, CA, USA) and normal DNA from Sigma (St Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…These were GCT27, GCT44, Tera1, Tera2, H12.2, 2102Ep, 577MF, NTERA2, SUSA and TCam-2. The cell lines were cultured as described previously (Pera et al, 1987;Kelland et al, 1992;Mizuno et al, 1993;Summersgill et al, 2001;Goddard et al, 2007). A pool of 45 individual samples of normal testis RNA was available from Clontech (Mountain View, CA, USA) and normal DNA from Sigma (St Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…KITLG-KIT pathway involvement in TGCTs is supported by numerous evidences: high expression of KIT, somatic activating mutations, and genomic amplification of KIT are frequently seen in TGCTs (especially seminomas; Izquierdo et al 1995, Strohmeyer et al 1995, Bokemeyer et al 1996, Rapley et al 2004, McIntyre et al 2005, Goddard et al 2007; germline deletions of Kitlg increase susceptibility to Table 4 Association of KITLG SNPs with sperm count in testicular germ cell tumor (TGCT) cases and controls TGCTs in mice (Heaney et al 2008); other than KITLG, two of the loci identified by GWAS (SPRY4 and BAK1; Kanetsky et al 2009, Rapley et al 2009 are involved in the KITLG-KIT pathway. The KITLG-KIT system is critical for the correct development of PGCs (Runyan et al 2006, Boldajipour & Raz 2007, the cells from which TGCT is believed to arise.…”
Section: Discussionmentioning
confidence: 94%
“…The induced activation of the kinase domain is mediated by receptor oligomerization 40 and the phosphorylated receptors stimulate intracellular signaling pathways controlling cell proliferation, adhesion, apoptosis, survival and differentiation, primarily through the RAS-RAF-MAPK and the PI3-K/AKT-mTOR cascades. 17,[41][42][43] The study of Hernando et al 17 surveying the activation of these pathways in sarcomas found 44 including 10 low-grade, 9 intermediate and 27 high-grade cases. A significant difference was found between the expression of IGF2 in the intermediate and the high-grade groups.…”
Section: Discussionmentioning
confidence: 99%